2016
DOI: 10.1590/1678-4162-8290
|View full text |Cite
|
Sign up to set email alerts
|

Características produtivas e nutricionais do capim-xaraés inoculado com bactérias diazotróficas associativas

Abstract: RESUMOO objetivo do trabalho foi avaliar as características produtivas e nutricionais do capim-xaraés inoculado com bactérias diazotróficas associativas, em primeiro cultivo em Latossolo Vermelho do Cerrado. O experimento foi realizado em casa de vegetação. O delineamento experimental foi inteiramente ao acaso, constituído por fatorial 6x3: três estirpes de bactérias diazotróficas associativas (MTAz8, MTH2 e Y2), uma combinação das estirpes MTAz8 e MTH2, adubação nitrogenada e testemunha absoluta, e três corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The reduction in CP content as a function of age may be related to the increase of the cellular appearance constituents, proportionally diluting the components present in the cellular content, a fact also observed by Bosa, Guimarães, Polizel, Bonfim-Silva and Canuto (2016) and Monção et al (2016). The CP content of 8.8% at the 49 days of regrowth verified in this research is satisfactory according to Van Soest (1994), who showed that the dry matter intake of tropical forages is positively influenced by the protein content of the plants, when this parameter is above 7%.…”
Section: Resultsmentioning
confidence: 67%
“…The reduction in CP content as a function of age may be related to the increase of the cellular appearance constituents, proportionally diluting the components present in the cellular content, a fact also observed by Bosa, Guimarães, Polizel, Bonfim-Silva and Canuto (2016) and Monção et al (2016). The CP content of 8.8% at the 49 days of regrowth verified in this research is satisfactory according to Van Soest (1994), who showed that the dry matter intake of tropical forages is positively influenced by the protein content of the plants, when this parameter is above 7%.…”
Section: Resultsmentioning
confidence: 67%
“…Biological nitrogen fixation (BNF) is performed through the nitrogenase enzyme present exclusively in diazotrophic bacteria, transforming N2 into ammonia (Moreira & Siqueira, 2006). They also reduce the need for chemical fertilizers (Bosa et al, 2016).…”
Section: Biological Nitrogen Fixationmentioning
confidence: 99%
“…However, the density and diversity of these microorganisms in the soil is influenced both by edaphoclimatic conditions and vegetation type (VITORAZI FILHO et al, 2012). Studies by Guimarães et al (2011) and Bolsa et al (2016) report the potential contribution of inoculation with some bacterial strains to the development of Brachiaria spp. Still, studies of inoculation with nitrogen-fixing bacteria in forage grasses are incipient, requiring in vitro research studies to identify desirable physiological properties in bacterial strains that could potentially promote grass growth and soil enrichment with a great success when applied in the field.…”
Section: Introductionmentioning
confidence: 99%